Investigating The Role of Transformational Leadership, Corporate Social Responsibility on Job Performance and Organizational Citizenship Behavior of Indonesian SMEs - Rafie Zaidan Prayuda; Rayyan Aqila Praditya (Journal of Industrial Engineering & Management Research, 2023)
This study aims to analyze the effect of transformational leadership on work performance and organizational citizenship behavior (OCB) which is mediated by corporate social responsibility (CSR). The research data was obtained by distributing questionnaires using a Likert scale with a total sample of 567 respondents. Sampling used a purposive sampling technique with the criteria of SMEs employees. Data were analyzed using PLS-SEM. The results of the research and discussion reveal that transformational leadership and CSR activities can improve employee performance and OCB, and CSR activities can mediate transformational leadership on employee performance and OCB. The results show that the existence of leadership that can inspire, build understanding and create a comfortable and safe work environment is a driving force in increasing voluntary behavior among employees and encouraging employees to complete their responsibilities for their work.